Business Incubators as Allied in Reducing the Transaction Costs in Mexican Entrepreneurs (British Journal of Multidisciplinary and Advanced Studies, 2022)
Strategic alliances are given by voluntary agreement between the parties, and have various forms, means and objectives which exist. In this text, the incubators as potential allies for entrepreneurs in the creation process of the company and as a cause of reduction of transaction costs in the process, where the relationship between the two sides have discussed them generates benefits of various natures. While it is not set as the union of both, if it looks like the relationship and close contact, as a network, which allows the incubator to survive and achieve its objective and entrepreneurial reduce the risk of birth as a company, in addition to build networks with other companies, organizations or institutions and ease of financing, and even the possibility of investors.
Keywords: Strategic Alliance; business incubator; entrepreneurship; transaction costs